Blood clot fracture properties are dependent on red blood cell and fibrin content. (June 2021) - Fereidoonnezhad, Behrooz; Dwivedi, Anushree; Johnson, Sarah; McCarthy, Ray; McGarry, Patrick
Abstract: Thrombus fragmentation during endovascular stroke treatment, such as mechanical thrombectomy, leads to downstream emboli, resulting in poor clinical outcomes. Clinical studies suggest that fragmentation risk is dependent on clot composition. This current study presents the first experimental characterization of the composition-dependent fracture properties of blood clots, in addition to the development of a predictive model for blood clot fragmentation. A bespoke experimental test-rig and compact tension specimen fabrication has been developed to measure fracture toughness of thrombus material. Fracture tests are performed on three physiologically relevant clot compositions: a high-fibrin clot made from a 5% haematocrit (H) blood mixture, a medium-fibrin clot made form a 20% H blood mixture, a low-fibrin clot made from a 40% H blood mixture. Fracture toughness is observed to significantly increase with increasing fibrin content, i.e. red blood cell-rich clots are more prone to tear during loading compared to the fibrin-rich clots. Results also reveal that the mechanical behaviour of clot analogues is significantly different in compression and tension. Finite element cohesive zone modelling of clot fracture experiments show that fibrin fibres become highly aligned in the direction perpendicular to crack propagation, providing a significant toughening mechanism. The results presented in this study provide the first characterization of the composition-dependent fracture behaviour of blood clots and are of key importance for development of next-generation thrombectomy devices and clinical strategies. Statement of significance: This study provides a characterisation of the composition-dependent fracture toughness of blood clots. This entails the development of novel experimental techniques for fabrication and testing of blood clot compact tension fracture specimens. The study also develops cohesive zone models of fracture initiation and propagation in blood clots. Results reveal that the fracture resistance of fibrin-rich clots is significantly higher than red blood cell rich clots. Simulations also reveal that stretching and realignment of the fibrin network should be included in blood clot material models in order to accurately replicate compression-tension asymmetry and fibrin enhanced fracture toughness. The results of this study have potentially important clinical implications in terms of clot fracture risk and secondary embolization during mechanical thrombectomy procedures. Graphical abstract: Image, graphical abstract